A systematic review of operating room ventilation. (August 2021) - Sadrizadeh, Sasan; Aganovic, Amar; Bogdan, Anna; Wang, Cong; Afshari, Alireza; Hartmann, Anne; Croitoru, Cristiana; Khan, Amirul; Kriegel, Martin; Lind, Merethe; Liu, Zhijian; Melikov, Arsen; et al.
Abstract: Ventilation systems are the primary way of eliminating airborne pathogenic particles in an operating room (OR). However, such systems can be complex due to factors such as different surgical instruments, diverse room sizes, various staff counts, types of clothing used, different surgical types and duration, medications, and patient conditions. OR ventilation should provide a thermally comfortable environment for the surgical staff team members while preventing the patient from suffering from any extreme hypothermia. Many technical, logistical, and ethical implications need to be considered in the early stage of designing a ventilation system for an OR. Years of research and a significant number of publications have highlighted the controversy and disagreement among infection specialists, design engineers, and ventilation experts in this context. This review article aims to provide a good understanding of OR ventilation systems in the context of air quality and infection control from existing research and provide multidimensional insights for appropriate design and operation of the OR. To this end, we have conducted a systematic review of the literature, covering 253 articles in this context. Systematic review and meta-analyses were used to map the evidence and identify research gaps in the existing clinical, practical, and engineering knowledge. The present study is categorized into six research focuses: ventilation system, thermal comfort, staff work practice and obstacles, door operation and passage, air cleaning technology, emission rate, and clothing systems. In the conclusion, we summarize the key limitations of the existing studies and insights for future research direction. Highlights: Majority of airborne particles found in surgical wounds come from the OR air. Surgical staff presented in the OR are the primary source of airborne bacteria. OR ventilation is the main tool to dilute and remove contaminants from the surgical zone. Selection between different types of OR ventilation is highly case-dependent and still controversial.